Alkaloid from Anona reticulata Linnaeus - Cachero, Ma. Luisa G.
Many members of the Family Anonaceae have been found to contain alkaloids. Of its 125 species contained in the genus Anona, extensive research have been done on Anona muricata Linn. (soursop) and Anona squamosa Linn. (sugar apple). As early as 1930, Alfredo C. Santos, upon examination of the bark of Anona reticulata L., found that it contains 0.03% anonaine. This alkaloid, melting at 122-123°C, had a formula of C17H16O3N. in a related work, Trimurti showed that anonaine was identical with the alkaloid from the seeds of A. squamosa L. muricine and muricimine, alkaloids isolated from A. muricata, are of a different structure but the researchers are in agreement that all four alkaloids are of the aporphine type.